FEATURES WIDTH FURROWS OF CEREBRAL HEMISPHERES IN PRACTICALLY HEALTHY YOUNG MEN AND WOMEN WITH VARIOUS SOMATOTYPE FROM PODILLYA Shevchuk Yu. H. - Шевчук, Ю.Г. (World of Medicine and Biology, 2015)
Individual variability based on variations of cerebral furrows in patients with different size of the skull which carries inducing effect on the shape and parameters of the latter. However, separate impact study of craniotipe as a display of personal constitution does not allow to fully appreciate the interconnections in the overall structure of the constitution, which represents one of the main objectives of anatomy and human biology.Aim of our work – define the features of computer-tomographic parameters furrows hemispheres of the brain in boys and girls with different somatotypes. Materials and methods82 almost healthy boys and 86 girls in the third generation residents of Podilskiy region of Ukraine conducted a CT scan of the head, lumbar spine on the median-sagittal cut and chest within the planned checkups by voluntary written consent of their parents or investigated (effective radiation dose does not exceed 1 mSv / year).Computed tomography of the head performed using spiral CT «SeleCT SP» company «Elscint» (Israel) (10 slices, voltage and amperage 120kV / 2-25mA - effective radiation dose 0,3 mSv). Conducted counting the number of visible scan on hemispheric furrows, determined the maximum width of each - perpendicular segment that connects the most distant points between the two neighboring gyri (right and left separately). Counted the average width furrows left and right hemispheres of a brain.Anthropometric survey of healthy young men and women were held by the scheme V. Bunak (1941). To evaluate the somatotype used mathematical scheme of J. Carter i B. Heath (2003).Statistical analysis of the results was done using the package "STATISTICA 6.1", which belongs to SRC VNMU named after Pirogov (license № BXXR901E246022FA), using parametric and non-parametric estimation methods. Results. DiscussionsIt is established that the value of the nearcentral sulcus width of left and right hemispheres of a brain at the level of T10 in girls with an average intermediate somatotype was significantly (p
Keywords: boys; girls; somatotype; grooves of brain